Innovative personality traits and their relationship to the psychological burnout of handball Premier League club coaches, a survey research - Mahmood Ahmed, Falah (International Journal of Psychosocial Rehabilitation, 2020)
The trend to study and teach innovation has become a global trend due to its positive results and effects on the progress of societies, especially that the challenges of the times call for taking creative positions, and it has become largely agreed upon among thinkers that the differences between developed and underdeveloped or developing nations are differences in the extent to which these Nations or their lack of innovative minds, so innovation has become the key to training in its fullest sense and the key to solving most of the intractable problems afflicting sports, especially handball. And the physical abilities that players acquire are strong threads that fit in their personalities and capabilities through his interaction with them, as research has proven that effective training depends primarily on the personality of the coach. Basic and physical abilities that depend mainly on the philosophy of each coach and the extent of his ability and innovation in training, and the term psychological burnout appeared in Recently in the sports field, we began to hear that a sports coach has suffered from physical, emotional and mental exhaustion, which comes as a result of dissatisfaction, boredom, distress and despair from this profession and the realization of failure to achieve the goals that the sports coach set for himself.Therefore, the importance of the research lies in studying the innovative personality traits and trying to know the type of relationship with the psychological burnout of handball coaches for the Premier League clubs in Iraq in order to reach final results that serve the game coaches and researchers in general and in the field of handball.